2013
DOI: 10.1007/s12471-013-0374-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training programs in Dutch cardiac rehabilitation centres

Abstract: Purpose To assess methods for determination of exercise intensity, and to investigate practice variation with respect to the contents, volume and intensity of exercise training programs in Dutch cardiac rehabilitation (CR) centres. Methods A paper questionnaire was sent to all Dutch CR centres, consisting of 85 questions for patients with an acute coronary syndrome (ACS) or after coronary revascularisation (Group 1) and for patients with chronic heart failure (CHF, Group 2). Results CR professionals from 45 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 24 publications
0
36
4
Order By: Relevance
“…A questionnaire was modified based upon a similar research study conducted among Dutch CR programs (3). Cardiac rehabilitation clinicians from 58 phase II facilities across the states of Illinois, Indiana, Michigan, Minnesota, Ohio, and Wisconsin completed the questionnaire over the phone.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was modified based upon a similar research study conducted among Dutch CR programs (3). Cardiac rehabilitation clinicians from 58 phase II facilities across the states of Illinois, Indiana, Michigan, Minnesota, Ohio, and Wisconsin completed the questionnaire over the phone.…”
Section: Methodsmentioning
confidence: 99%
“…Second, this guideline provides clear practical guidance on how to tailor exercise with respect to intensity and duration individually, using results of a maximum or symptom-limited exercise test. In this way we aim to reduce the considerable practice variation which has recently been reported in Dutch CR centres [11], and thereby, to increase effectivity of exercise-based CR in the Netherlands [10]. A third novel topic is the addition of HIT as a training strategy in CHD patients.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Recently, it was reported that among Dutch CR centres, considerable variation exists in methods for determination of exercise intensity, training intensity and volume, and uniformity of physiotherapeutic interventions [11]. A possible explanation for this is that both the 2011 multidisciplinary CR guideline [12] and the 2005 CR guideline by the Dutch Royal Society for Physiotherapists (KNGF) [13] lack clear practical guidance for PTs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the already low uptake of CR in the Netherlands median total training duration seems to be less than 3 months [10, 11]. Consolidating lifestyle habits require continued attention and appropriate guidance [3].…”
Section: Introductionmentioning
confidence: 99%